CSF-Progranulin and Neurofilament Light Chain Levels in Patients With Radiologically Isolated Syndrome—Sign of Inflammation - Pawlitzki, Marc; Sweeney-Reed, Catherine M.; Bittner, Daniel; Lux, Anke; Vielhaber, Stefan; Schreiber, Stefanie; Paul, Friedemann; Neumann, Jens (Frontiers in Neurology, 2018)
Background: Cerebrospinal fluid (CSF) markers of disease in patients with radiologically isolated syndrome (RIS) are the subject of intense investigation, because they have the potential to enhance our understanding of the natural disease course and provide insights into similarities and differences between RIS and other multiple sclerosis (MS) disease identities. Methods: Here we compared neurofilament light chain (NFL) and progranulin (PGRN) levels in the CSF in RIS patients with levels in patients with different subtypes of MS and healthy controls (HC) using Kruskal–Wallis one-way analysis of variance. Results: Median CSF NFL concentrations in RIS patients did not differ to those in HC and clinically isolated syndrome (CIS) patients, but were significantly lower than in relapsing remitting (RRMS) and primary progressive (PPMS) MS patients. In contrast, RIS patients exhibited higher median CSF PGRN levels than HC and showed no significant differences compared with CIS, RRMS, and PPMS cases. Conclusion: We postulate that elevated PGRN values in the CSF of RIS patients might indicate inflammatory and repair activity prior to axonal disintegration.